Quantitative geodiversity assessment in biodiversity investigations - Maija Toivanen (Nordia Geographical Publications, 2024)
Despite the growing recognition of geodiversity in recent years, it remains overshadowed by its biotic counterpart, biodiversity. The objective of this thesis is to narrow this gap by advancing the quantitative assessment of geodiversity within the context of biodiversity.  The main objective is to provide a theoretical and methodological framework for the study of landscape-scale geodiversity in biodiversity investigations, with some insights for nature conservation.